Artemisin Combined Therapy in malaria patients: Do we need to search for more? - Chinmay Jani; Neil Palkhiwala; Ami Parikh; Nilay Suthar; Khushali Patel (International Journal of Medical Research and Review, 2018)
Introduction: Malaria is a vector borne disease highly prevalent in the topical developing countries. Two main species of plasmodium causing majority of diseases manifestations are P. Vivax and P. falciparum. The approach to antimalarial selection is determined based on the location of the patient. For treatment of uncomplicated P. falciparum malaria, according to WHO guidelines first line therapy mainly includes Artemisin Combined Therapy. Concerns about the emergence of resistance to artemisin derivatives have increased recently. The main aim of the present study is to investigate the effect of using a combination of intravenous artesunate along with oral doxycycline, as a novel ACT for Malarial infections – falciparum vs. vivax.Methodology: Prospective observational study was carried out at V S General Hospital in Ahmedabad, Gujarat, India. A full history of current illness was taken followed by examining the serial peripheral smear reports of the patients till the malarial parasites are not seen on two consecutive occasions. Samples were taken at least 6 hours apart by the capillary method and oral temperature was measured every 6 hours. We excluded other associated viral fevers such as dengue, pediatric age group (<12 years) and Co-Morbid illnesses like hepatic or renal dysfunction. Data analysis was done using SPSS software version 20.Results: Student t test showed that PCT was significantly more in falciparum (mean= 74.53 hours) patients as compared to vivax patients (mean= 51.89 hours). (p<0.001). Also duration of stay was significantly more in patients having falciparum (mean =3.63 days) as compared to patients having vivax (mean = 2.32 days) (p<0.001) Multivariate analysis by linear regression showed that species of the parasite was the most significant independent predictor (B=12.552) of the time to parasite clearance and other significant variable was Grade of parasitemia at 0 hour (B= 12.798). We also found that patients with residual parasitemia was 83.78 %, 40.54% and 10.81% in vivax group whereas it was 100%, 88.15% and 46.05% in falciparum respectively at 24, 48 and 72 hours.Conclusion: The study shows that PCT and residual parasitemia is very high in falciparum patients as compared to previous reports of different studies and also as compared to vivax group patients. ACT resistance is a grave concern for falciparum and more studies should be done to understand pathophysiology and its prevalence in India. We strongly suggest that a continues monitoring needs to be implemented in health policy to understand the dynamicity of emerging resistance